2015
DOI: 10.1017/s0030605315000393
|View full text |Cite
|
Sign up to set email alerts
|

Household livelihoods and conflict with wildlife in community-based conservation areas across northern Tanzania

Abstract: Conservation strategies to protect biodiversity and support household livelihoods face numerous challenges. Across the tropics, efforts focus on balancing trade-offs in local communities near the borders of protected areas. Devolving rights and control over certain resources to communities is increasingly considered necessary, but decades of attempts have yielded limited success and few lessons on how such interventions could be successful in improving livelihoods. We investigated a key feature of household we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 46 publications
1
38
1
Order By: Relevance
“…The success record of CBNRM in general is highly variable (Kellert et al , Tallis et al , Brooks et al , Brooks ), and the socio‐economic performance of WMAs has been criticized (Benjaminsen et al , Bamford et al , Bluwstein et al , Moyo et al ). However, evidence is beginning to indicate that positive social and ecological outcomes can result from WMA projects (Tetra Tech and Maliasili Initiatives , Pailler et al , Salerno et al , Lee and Bond ). My data have demonstrated that WMA establishment and management in Tanzania as practiced in Burunge WMA had positive outcomes for wildlife species densities and demographic rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The success record of CBNRM in general is highly variable (Kellert et al , Tallis et al , Brooks et al , Brooks ), and the socio‐economic performance of WMAs has been criticized (Benjaminsen et al , Bamford et al , Bluwstein et al , Moyo et al ). However, evidence is beginning to indicate that positive social and ecological outcomes can result from WMA projects (Tetra Tech and Maliasili Initiatives , Pailler et al , Salerno et al , Lee and Bond ). My data have demonstrated that WMA establishment and management in Tanzania as practiced in Burunge WMA had positive outcomes for wildlife species densities and demographic rates.…”
Section: Discussionmentioning
confidence: 99%
“…I used data I collected from 2012 to 2017. Details of WMA history and management structure are given elsewhere (Benjaminsen et al , Tetra Tech and Maliasili Initiatives , Moyo et al , Salerno et al ).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Community-based natural resource management models have been advocated as a dual strategy to alleviate poverty and to halt overall biodiversity decline (Berkes, 2004(Berkes, , 2007Kiss, 1990Kiss, , 2004. In East Africa, where wildlife populations have been declining (Craigie et al, 2010;Stoner et al, 2007;Western, Russell, & Cuthil, 2009) and people in rural areas often lack basic commodities (Ellis & Freeman, 2004;Reardon & Vosti, 1995;Salerno, Borgerhoff Mulder, Grote, Ghiselli, & Packer, 2016), community-based wildlife conservation models have been considered and implemented as a strategy to balance the trade-off between wildlife conservation and development (Borgerhoff Mulder & Coppolillo, 2005;Kiwango, Komakech, Tarimo, & Martz, 2015;Naidoo et al, 2016). In East Africa and elsewhere, such community-based conservation models have been subject to considerable criticism, specifically in regard to their socio-economic contributions and poor governance (Benjaminsen, Goldman, Minwary, & Maganga, 2013;Bluwstein, Moyo, & Kicheleri, 2016;Brehony, Bluwstein, Lund, & Tyrrell, 2018;Goldman, 2003;Moyo, Ijumba, & Lund, 2016;Wright, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Lamsal et al (2015) suggested that better-off households who had less dependence on wetland resources were more involved with conservation organisations. A similar contribution of linkages between less direct benefits of wildlife management areas and more direct engagement with policy process was found in northern Tanzania by Salerno et al (2015).…”
Section: Discussionmentioning
confidence: 57%